CENTRAL POLITICS, GERMAN IMMIGRATION AND LITTLE PEOPLE AT THE NINETEENTH-ONIC BORDER. VALDIVIA, LA UNIÓN AND OSORNO (1840-1890) - Muñoz Sougarret, Jorge (Revista de Historia Social y de las Mentalidades, 2025)
For the historiography the south border of the araucanía has suffered, during the second half of the 19th century, a point unique of notable inf lexion, the arrival of german immigrants. of equal way, the rest of the local population has appeared in a background, often so much as shackler or extra of the impulses developer of the colonists. Knowing the previous thing, and without expecting to generate a diametrical change, we have centred on this work on such populations of natives, how they were affected by the immigration and how they faced the relating to the moment changes that shook the foundations of his society.